Enablers of strong cookstove sales through a purchase offer approach in rural Senegal: An explorative analysis - Gunther Bensch; Jörg Peters (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
The use of well-designed improved cookstoves (ICS) in regions devoid of modern energy yields high private and social returns, mostly related to considerable woodfuel savings. Take-up rates are nonetheless often very low when people have to pay costcovering prices. This paper presents main results of a study in rural Senegal where households were individually invited to purchase ICS in their villages. Households' ICS purchases and willingness to pay levels turned out to be unexpectedly high. We therefore explore potential factors behind this surprisingly high adoption, particularly those features of our approach that deviate from common real-world ICS markets. We observe that especially the way we designed our personalized door-to-door sales offer is an important determinant. Based on our findings, we derive insights for the design of future ICS dissemination programs. – – Die Nutzung verbesserter Kochherde vermag sich in Regionen ohne Zugang zu moderner Energie sehr positiv auf das individuelle wie auch gesellschaftliche Leben auswirken, vor aufgrund direkter wie indirekter Effekte erheblicher Holzeinsparungen. Der Verbreitungsgrad solcher Herde ist jedoch oftmals sehr gering sobald kostendeckende Preise gezahlt werden müssen. Dieses Papier präsentiert zentrale Ergebnisse einer Studie im ländlichen Senegal, im Rahmen derer Preisgebote für zuvor präsentierte verbesserte Kochherde von Haushalten individuell eingeholt wurden. Die beobachtete Zahlungsbereitschaft und die resultierenden Herdverkaufszahl erwiesen sich als unerwartet hoch. Wir untersuchen daher potenzielle Faktoren, die diesem überraschend hohen Annahmeverhalten zugrunde liegen können. Wir betrachten insbesondere jene Merkmale unseres Verbreitungsansatzes, die von üblichen Märkten für Kochherde abweichen. Wir beobachten, dass vor allem bestimmte Details unseres individuellen Verkaufsangebots wichtige Bestimmungsgrößen darstellen. Basierend auf unseren Erkenntnissen leiten wir Empfehlungen für die Gestaltung zukünftiger Kochherd-Verbreitungsprogramme ab.
Keywords: D12; D83; O13; O33; Q41; 330; Energy access; technology adoption; willingness to pay; rural Africa